South African small business growth through interfirm linkages - Toomey, David Colbert (Rhodes University, Faculty of Humanities, Department of Political Studies, 1999)
Economic stagnation in sub-Saharan Africa since 1970 is well documented. While the causes are varied, the paradigm of nationalistic state-led economic development has changed. Economic development occurs in a global marketplace. Manufacturing has shifted from developed to less developed countries, an opportunity that was seized in Asia and Latin America. South Africa's labour, unskilled and costly by world standards, is at a disadvantage as an agile and competitive world market seeks skilled labour at the lowest cost. South Africa's Gear economic policy suggests that 300 000 new jobs need to be created annually until 2004 in order to reduce unemployment. Small, medium and microenterprise growth is central to meeting this target. Numerous government structures to assist small enterprises have been created. Few, however, assist small business with the demands of the marketplace. Most focus on generic skills training and questionable small business finance. This thesis suggests that interfirm linkages between large and small enterprises is one strategy that can assist the growth of small business, create employment and, increase labour skills. International experience shows that generic training is less effective in promoting small business than linking business training to actual market-demands. Interfirm linkages, most often through subcontracting, is a strategy used successfully in Taiwan, Indonesia, Malaysia and Brazil. Such linkages are usually government supported and provide incentives for both large and small businesses to work together productively. Three South African interfirm linkage case studies are critiqued. Case study findings indicate that interfirm linkages expose emerging businesses to market conditions, and can provide access to process technology training, low cost raw materials, creative finance, and new markets. Small business 'learns by doing' and also 'learns while earning'. The state has a role in the development of a vibrant small, medium and microenterprise sector in South Africa. Current support strategies are largely unrelated to market conditions. Interfirm linkages are an approach that applies market forces in the development of small business. Government policy would be wisely directed to support such business interactions.
Keywords: Small business -- South Africa; Interorganizational relations; Small business -- South Africa -- Growth -- Case studies; South Africa -- Economic policy